Fabrication of Sand Brick with Additive of Waste Thermoplastic Composition - HAMZAH, ZAHIRAH; AHMAD, SAID (Research Progress in Mechanical and Manufacturing Engineering, 2022)
As Malaysia is overburdened with waste materials, plastic waste can be used as a replacement in the production of brick as brick is one of the most common important units as a building material. The main objective of this project is to develop a sand brick with an additive of thermoplastic composition waste which is PET. Using the property of mechanically recyclable, the PET bottles will be mixed with sand and cement in a different ratio in a range between 5% to 15%. The ratio of cement, sand and PET waste is 1: 5.7/5.4/5.1: 0.3/0.6/0.9 respectively. After that, the plastic sand brick will undergo a few tests such as bulk density, water absorption test and compressive strength test after 7 days of curing process. The comparison result between sand brick with PET and the conventional sand brick from the local hardware store was evaluated. From the result, it shows that brick with 10% of PET waste shows the highest average bulk density which is 2341.67 kg/mm3. The lowest average water absorption among the plastic sand brick was recorded by 10% of PET waste which is 9.68% but it is higher than the conventional sand brick which only had an average of 4.01%. The compressive strength decreases as the percentage of PET waste increases. The results obtained from this project are expected to help determine the appropriate mixing ratios of sand, cement and plastic in order to obtain a good brick.